Miskwabik, Metal of Ritual : Metallurgy in Precontact Eastern North America. - Trevelyan, Amelia M. (The University Press of Kentucky, 2004)
Miskwabik, Metal of Ritual examines the thousands of beautiful and intricate ritual works of art -- from ceremonial weaponry to delicate copper pendants and ear ornaments -- created in eastern North America before the arrival of Europeans. The first comprehensive examination of this 3,000-year-old metallurgical tradition, the book provides unique insight into the motivation of the artisans and the significance of these objects, and highlights the brilliance and sophistication of the early civilizations of the Americas.Comparing the ritual architecture and metallurgy of the original Americans.